Juventudes rurales - Vallejo Hidalgo, Nicolás; Martínez Godoy, Diego (Pontificia Universidad Católica del Perú, 2023)
The present article critically examines how rurality has transformed in the context of globalization, and its effects on rural youth in Ecuador, based on an intertemporal analysis of the National Survey of Employment, Unemployment and Underemployment, as well as relevant case studies that directly or indirectly focus on youth. The article aims to provide a conceptual framework for understanding rural youth that goes beyond narrow definitions based solely on age and challenges urban-centric, homogenizing, and adult-centered notions. Accordingly, drawing on theoretical perspectives on territorial development, the article identifies three major challenges that rural youth pose for rural territorial development.

El presente artículo analiza las principales transformaciones de la ruralidad, en el marco de la globalización, y sus impactos en las juventudes rurales de Ecuador, a través del análisis intertemporal de la Encuesta Nacional de Empleo, Desempleo y Subempleo, y de casos de estudio que abordan directa o indirectamente a las juventudes. Se busca realizar una aproximación conceptual de las juventudes rurales que permita superar las definiciones que tienden a reducir a las juventudes a un determinado rango de edad, y las nociones urbano céntricas, homogeneizantes y adultocéntricas. De esta manera, a partir de una conceptualización teórica del desarrollo territorial, se esbozan tres grandes desafíos que presentan las juventudes rurales para el desarrollo territorial rural.
Rural Youth
Keywords: Rural youth; Territorial transformations; Rural territorial development; Ecuador; Juventudes rurales; Transformaciones territoriales; Desarrollo territorial rural; Ecuador; https://purl.org/pe-repo/ocde/ford#5.04.00